2016
DOI: 10.1016/j.rbmo.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bariatric surgery on semen parameters and sex hormone concentrations: a prospective study

Abstract: Obesity has become a major health concern, with a prevalence rate approaching epidemic states. An inverse relationship between men's body weight and semen parameters has been observed, suggesting a favourable role for weight loss in improving fertility. This prospective study included 46 patients undergoing sleeve gastrectomy, who were investigated with semen analysis and serum hormone tests before and 12 months after surgery. Patients were divided into three groups according to their initial sperm concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 20 publications
2
65
0
2
Order By: Relevance
“…A meta‐analysis that included studies based on lifestyle changes and surgical interventions including bariatric surgery found similar results of better testosterone profiles in those who underwent these interventions (Corona et al., ). Additionally, a recent prospective study found improvement in semen parameters in azoospermic and oligospermic men after bariatric surgery (El Bardisi et al., ). Furthermore, reverting to nonobese states normalised sperm microRNA profiles and metabolic syndrome in the offspring of obese fathers was observed (McPherson, Fullston, Aitken, & Lane, ; McPherson, Owens, Fullston, & Lane, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis that included studies based on lifestyle changes and surgical interventions including bariatric surgery found similar results of better testosterone profiles in those who underwent these interventions (Corona et al., ). Additionally, a recent prospective study found improvement in semen parameters in azoospermic and oligospermic men after bariatric surgery (El Bardisi et al., ). Furthermore, reverting to nonobese states normalised sperm microRNA profiles and metabolic syndrome in the offspring of obese fathers was observed (McPherson, Fullston, Aitken, & Lane, ; McPherson, Owens, Fullston, & Lane, ).…”
Section: Discussionmentioning
confidence: 99%
“…If BMI ≥40 kg/m 2 , bariatric surgery is the choice of treatment as several studies shown beneficial effects in patients who underwent gastric bypass surgeries with resultant improvement in increased serum testosterone and sperm count (Reis et al. , El Bardisi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the adverse consequences of obesity and the possible negative role of male BMI, the benefits of weight reduction should be discussed when counselling couples interested in fertility treatment. Analogous to some clinical conditions such as cardiovascular diseases or diabetes, it is believed that weight loss can benefit male fertility, helping to restore normality of hormonal profiles (ASRM, ; El Bardisi et al., ). However, existing data on the benefits of weight loss are unclear, and it should be noted the lack of well‐designed studies that demonstrate improvement in seminal quality with BMI reduction (ASRM, ; El Bardisi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous to some clinical conditions such as cardiovascular diseases or diabetes, it is believed that weight loss can benefit male fertility, helping to restore normality of hormonal profiles (ASRM, ; El Bardisi et al., ). However, existing data on the benefits of weight loss are unclear, and it should be noted the lack of well‐designed studies that demonstrate improvement in seminal quality with BMI reduction (ASRM, ; El Bardisi et al., ). On the other hand, abrupt weight loss with restriction of intake/absorption of important nutrients can lead to worsening seminal quality (El Bardisi et al., ; Sermondade, Massin, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…4 Higher adiposity and weight gain are strong risk factors for gout in men, while weight loss is protective. 5 Obesity adversely affects male fertility and can induce azoospermia, oligospermia and reduced testosterone levels; however, a 6 Sexual function is known to be problematic in obesity, erectile dysfunction in particular. 7 Although obesity is linked to an increased risk of several cancers, including colon, gallbladder, kidney, and pancreas, its role in prostate cancer aetiology remains uncertain, with inconsistent data.…”
Section: Wwwtrendsinmenshealthcom Trends In Urology and Men's Health mentioning
confidence: 99%